Synthesis of low shrinkage monolith alumina aerogels by surface modification and ambient pressure drying. (1st September 2018) - Li, Chi; Gong, Zheng; Ding, Likang; Guo, Donglai; Hu, Wenbin
Abstract : The authors have synthesised a kind of low shrinkage alumina (Al2 O3 ) aerogel using an inexpensive salt of aluminium (AlCl3 ·6H2 O) via tetraethoxysilane modification and an ambient pressure drying process. The morphology, pore structure, surface group, crystal phase and thermal properties of the Al2 O3 aerogel are analysed by X‐ray diffractometer, scanning electron microscopy, Fourier transform infrared spectra and nitrogen adsorption test. Further improvement in thermal stability and thermal shrinkage are obtained by incorporation of silicon (Si) atoms during the aerogel preparation. The specific surface area of modified aerogel is 480 m 2 /g and the diameter shrinkage is 8% after drying, and reach 304 m 2 /g and 16.5% after heating at 1000°C. The approach, which is straightforward, inexpensive and safe, can be employed to prepare a monolithic mesoporous material with low shrinkage and high‐temperature resistance. This will further promote the potential application of packaging and thermal insulation materials.